Isolation and optimization to enhance anti-Streptococcus suis bacteriocin production by Lactobacillus plantarum RB01-SO - Showpanish, K.; Sonhom, N.; Janyaphisan, T.; Woraprayote, W.; Rumjuankiat, K. (International Journal of Agricultural Technology, 2022)
One hundred and twenty lactic acid bacteria (LAB) isolated from traditional Thai fermented vegetable products were tested against Streptococcus suis an important food borne pathogen causing severe disease in pig farming and consumers. Only one isolate designated as “RB01-SO” inhibited S. suis, and also Bacillus subtilis, Enterococcus faecalis, Lactobacillus sakei, Lactococcus lactis, Listeria innocua, Listeria monocytogenes, Micrococcus luteus, Staphylococcus aureus, Streptococcus agalactiae, Aeromonas veronii, Escherichia coli, Pseudomonas aeruginosa, Salmonella Typhimurium and Vibrio harveyi. Inhibitory activities of RB01-SO cell free supernatant (CFS) were completely destroyed by various proteolytic enzymes including trypsin, α-chymotrypsin and pepsin, indicative of the proteinaceous or bacteriocin nature of the antimicrobial substance of RB01-SO. Bacteriocin production was highest when strain RB01-SO was cultured in MRS broth supplemented with 1% NaCl and initial pH of 7.0. Highest anti-S. suis activity of 400 AU/mL was obtained from the CFS after the bacterium was incubated at 30°C for 12 h at the above mentioned condition. Anti-S. suis activity of the CFS still remained after freeze-drying, suggesting its stability under the drying process. LAB that produced anti-S. suis agent with promising characteristics were successfully screened and isolated and showed potential for use in the food and feed industries